2002
DOI: 10.1067/mtc.2002.119702
|View full text |Cite
|
Sign up to set email alerts
|

Risk factor analysis for proximal and distal reoperations after surgery for acute type A aortic dissection

Abstract: Patients with acute type A aortic dissection who have severe aortic valve insufficiency are at increased risk for proximal reoperation. These patients should benefit from a more aggressive proximal repair at initial operation. Distal extent of aortic resection at initial operation did not significantly influence the risk of distal reoperation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
107
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(116 citation statements)
references
References 30 publications
6
107
0
Order By: Relevance
“…Our relatively conservative surgical approach seems to be reasonable for patients experiencing at least one of various preoperative complications, or elderly, from previous reports showing that elderly patients tended to have a thrombosed false lumen after initial surgery for AAAD. 8) Ten-year survival rates ranged from 37% to 71% in previously reported cases, 11,[15][16][17][18] 77% survival rate at 10 years in our institution seems acceptable. DeBakey et al reported that rupture of the distal aorta was the most common cause of death among patients with AAAD, accounting for 29.3% of 205 late deaths.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our relatively conservative surgical approach seems to be reasonable for patients experiencing at least one of various preoperative complications, or elderly, from previous reports showing that elderly patients tended to have a thrombosed false lumen after initial surgery for AAAD. 8) Ten-year survival rates ranged from 37% to 71% in previously reported cases, 11,[15][16][17][18] 77% survival rate at 10 years in our institution seems acceptable. DeBakey et al reported that rupture of the distal aorta was the most common cause of death among patients with AAAD, accounting for 29.3% of 205 late deaths.…”
Section: Discussionmentioning
confidence: 99%
“…11,[15][16][17][18][19] Larger numbers of patients with a longer follow-up period may be recommended for further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Second, a long aortic root remnant has by itself a dilatation risk due to cystic medial necrosis that is diffusely present in the aortic structure and which is the primary reason for aortic dissection [Marsalese et al, 1990]. Third, the use of gelatine-resorcinol-formaldehyde has been incriminated in a higher incidence of false aneurysms or re-dissections, particularly in the proximal part of the aorta [Kirsch et al, 2002]. For all these reasons, some authors have strongly recommended total aortic root replacement by a composite graft, subsequently to eliminate the entire diseased aortic root [Ergin et al, 1996].…”
Section: Discussionmentioning
confidence: 99%
“…The regions with the highest risk of developing an aneurysm are the distal arch and proximal descending thoracic aorta (DTA) (17,(22)(23)(24). In patients undergoing DBT1-AAD repair, freedom from aortic reoperation at 10 years ranges from 61% to 74% (10,20,25). To reduce the frequency of late aneurysm formation and reoperation, some surgeons have been motivated to perform more aggressive primary operations, all associated with strengths and weaknesses.…”
Section: Perspectivementioning
confidence: 99%
“…Given the high risk profile of patients with acute aortic dissection and the technical complexity of the necessary interventions, a conservative tear-oriented aortic replacement (more often a supra-coronary ascending/ hemiarch replacement) with commissural resuspension and re-establishment of the dominant blood flow in the distal true lumen currently represents the most common surgical approach. However, it has been demonstrated that the distal false lumen remains patent in about 70% to 80% of patients undergoing surgery for DBT1-AAD dissection (5)(6)(7)(8), and a wide and patent false lumen worsens the prognosis (6,(9)(10)(11)(12)(13)(14)(15)(16) by increasing the risk of late death, re-intervention and aneurysmal dilatation of the remaining dissected aorta (6,(17)(18)(19)(20)(21). The regions with the highest risk of developing an aneurysm are the distal arch and proximal descending thoracic aorta (DTA) (17,(22)(23)(24).…”
Section: Perspectivementioning
confidence: 99%